(untitled) (Research, Society and Development, 2021)
This article, the result of a master’s dissertation in education, aims to reflect on the incorporated cultural and musical social capitals their impacts for the emergence of interest in music, as well as, to understand the influences of the family, the school and the Cultural industry for the referred process. An exploratory research and multiple case study were carried out with two students from the first year of high school at a school in Fortaleza / Ceará. We used as a theoretical contribution the concepts of Pierre Bourdieu - Habitus, Campos e Capitais (2009, 2011a, 2011b, 2013), the Cultural Industry of Adorno and Horkheimer (1985) and the Culture of Pasta by Edgar Morin (2011). Through the narratives of life and musical formation, it was evidenced the fundamental and decisive role of the family for the emergence of interest in music, as well as the assistance and interference of the Cultural Industry in this process. Finally, the school showed little participation in this process.